Development and Validation of an RP-HPLC Method for Estimation of Tizanidine Hydrochloride in Pharmaceutical Dosage Forms - Saini , Ritika; Nagarajan, K.; Kaurav, Monika; Kamboj, Surbhi (Journal of Neonatal Surgery, 2025)
Tizanidine hydrochloride is a central muscle relaxant that acts as an agonist for centrally activating alpha-2 adrenoreceptors. It works for the treatment of spasticity, which is a neurological condition. Therefore, along with the increasing use of this drug, its quantification in the pharmaceutical formulation becomes essential for the drug quality control and regulatory purposes. A common way to detect it is using the tizanidine hydrochloride assay using liquid chromatography. In this study, qualitative and quantitative analysis-based RP-HPLC method was developed and validated for the estimation of tizanidine hydrochloride. The measurement of all tizanidine hydrochloride samples was performed on a C18 column, chromatographic separation was accomplished with an acetonitrile-phosphate buffer pH 7.5 (80:20 v/v) as the mobile phase at a flow rate of 1.5 mL/min during detection period. For detection purpose, use of UV detector was made at working wavelength of 230nm. The current procedure was verified in compliance with the ICH recommendations for a wide variety of parameters including specificity, linearity, precision, robustness and system suitability. The developed method shows suitable linearity at different concentration ranges with a correlation coefficient (R²) of 0.998. The precision was confirmed by low relative standard deviations (%RSD) for intra- and inter-day analyses. The robustness of the approach was evaluated through slight intentional changes in the chromatographic conditions which indicated no significant influence on the results. In conclusion, the suggested method using RP-HPLC is appropriate for routine evaluation of pharmaceutical formulations and bulk tizanidine hydrochloride because of its simplicity and precision.